MONETARY POLICY AGAINST REVIEW FROM AN ISLAMIC PERSPECTIVE - Maryam Batubara; Mukhlis (CV. Radja Publika, 2023)
Monetary policy was designed by the Indonesian government in 1953 based on Law no. 11 of 1953 concerning Principles of Bank Indonesia as a substitute for Javasche Bank Wet of 1922. Law No. 11 of 1953 was the basis for the formation of the Monetary Board in which the Minister of Finance acted as Chairman, while the Minister of Economy and the Governor of Bank Indonesia as Members. The Monetary Board has duties and powers closely related to controlling monetary conditions. According to the Big Indonesian Dictionary (KBBI) monetary is where the value of the currency greatly influences economic conditions. At the time of the Prophet, the monetary policy was implemented by using the standard bimetallic, namely gold and silver (dirhams and dinars) because both of them were legal tender and circulated in society.